2003
DOI: 10.1128/aem.69.6.3617-3625.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Genomic Regions (Quantitative Trait Loci) Controlling Production and Quality in Industrial Cultures of the Edible Basidiomycete Pleurotus ostreatus

Abstract: Industrial production of the edible basidiomycete Pleurotus ostreatus (oyster mushroom) is based on a solid fermentation process in which a limited number of selected strains are used. Optimization of industrial mushroom production depends on improving the culture process and breeding new strains with higher yields and productivities. Traditionally, fungal breeding has been carried out by an empirical trial and error process. In this study, we used a different approach by mapping quantitative trait loci (QTLs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…We also observed that the earliest hybrids tended to produce a higher number of smaller mushrooms, as already underlined by Xu (38), with production spread throughout the whole cropping period. Similar relationships between these productive traits have been described in another edible mushroom, P. ostreatus (15). This variability in earliness could be useful in developing new hybrid strains that cover the range of commercial mushroom outlets.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We also observed that the earliest hybrids tended to produce a higher number of smaller mushrooms, as already underlined by Xu (38), with production spread throughout the whole cropping period. Similar relationships between these productive traits have been described in another edible mushroom, P. ostreatus (15). This variability in earliness could be useful in developing new hybrid strains that cover the range of commercial mushroom outlets.…”
Section: Discussionmentioning
confidence: 56%
“…If numerous QTL analyses related to life history traits have been reported for various fungi (4,(17)(18)(19)34), those concerning yield-related traits in edible mushrooms are scarcer. In the oyster mushroom, Pleurotus oestratus, QTL controlling the growth rate, biomass production, and several production traits have been described (15,16,29). Although the button mushroom, Agaricus bisporus (Lange) Imbach, is the most widely cultivated edible mushroom species in Europe and North America (28), little is known about the genetic bases of important agronomic traits.…”
mentioning
confidence: 99%
“…depends on improving the culture process (Larraya et al, 2003). There are various additives that are known to stimulate fruiting.…”
Section: Introductionmentioning
confidence: 99%
“…Kwan and Xu (2002) employed quantitative trait locus (QTL) analysis to examine the growth rate of monokaryotic strains. Agronomic traits have also been characterized by QTL analysis in other edible basidiomycetes, Agaricus bisporus and Pleurotus ostreatus (Moquet et al 1999, Larraya et al 2002, 2003.…”
Section: Introductionmentioning
confidence: 99%